Evaluation of anthropometric indices and their relationship with maternal nutritional literacy and selected socio-economic and demographic variables among children under 5 years old - Mina Maheri; Maryam Bidar; Hamidreza Farrokh-Eslamlou; Ali Sadaghianifar (BMC, 2022)
Abstract Background Considering the destructive effects of malnutrition on the growth, development, and health of children and the importance of identifying the factors affecting it, the present study aimed to investigate the status of anthropometric indices and their relationship with maternal nutritional literacy and selected socio-economic and demographic variables among children under 5 years old. Methods This cross-sectional study was conducted on 405 mothers with children under 5 years old in Urmia, Iran. The data collection tool consisted of two parts. The first part was the demographic and socio-economic information of mother and child and the second part was the Evaluation Instrument of Nutrition Literacy on Adults; EINLA. Results There was statistically significant relationship between maternal nutritional literacy with weight-for-age, height-for-age, and weight-for-height indices; between weight-for-age index with maternal education, gestational weight gain, and mean weight, as well as mean height of the mother; between weight-for-age and weight-for-height indices with child gender, type of milk consumed, status of starting complementary foods, and history of acute respiratory infection, as well as diarrhea; and finally between height-for-age with family income status. Conclusions It is suggested that mothers with low nutritional literacy, mothers whose gestational weight gain was not normal, children whose family income is low, boy child, children with a history of disease, children who consume powdered milk and children who have not started complementary foods at the right time be given priority when designing and implementing educational interventions to enhance nutritional status and anthropometric indices of children.